Beyond the Speed of Light – A Review of the Theory of Relativity and the Speed of Light by the Ether (Dark Matter) - Lee, Hyun-Chun (Fundamental Research and Application of Physical Science Vol. 1, 2023)
We discover that the ether (dark matter), the medium of light, is a being influenced by gravity. We claim that the Michelson-Morley experiment is inappropriate for determining the ether (dark matter). Using classical mechanics, we calculate the deflection angle of starlight passing around the Sun by assigning a mass to a unit volume of the ether (dark matter) that mediates light waves. The results show that it is a more accurate calculation method than the angle of deflection of starlight proposed by Einstein's general theory of relativity. This demonstrates that ether (dark matter) has an infinitely small mass. If the ether (dark matter) exists, Einstein's definition of light may be invalid. We challenge the absoluteness of the speed of light and conclude with two new proposals.